Gingival lymphatic malformation. An atypical case report - Alberdi-Navarro, J.; Ruiz-Ochoa, N.; De Juan-Galindez, A.; Uribarri-Etxebarria, A. (Journal of clinical and experimental dentistry, 2023)
Lymphatic malformations are a rare pathology that presents a highly variable clinical expression. Intraorally, it mainly affects the dorsum of the tongue. The objective of this work is to present a case of lymphatic malformation in an atypical location. A 20-year-old male who attended the clinic for multiple vesicular lesion in attached gingiva, asymptomatic and of unknown evolution. Removal of the lesion and subsequent histological analysis were performed, which showed a microcystic lymphatic vascular lesion. Immunohistochemistry for D2-40 was performed, which corroborated the lymphatic origin of the lesion. At 6 months, no recurrence of the lesion was recognized. Clinicians should include lymphatic malformations in the differential diagnosis of multiple vesicular lesions. Knowing the oral manifestations of this entity is essential for its proper diagnosis and clinical management. Gingiva, oral lymphatic malformation, diagnosis.